2017
DOI: 10.18632/oncotarget.16215
|View full text |Cite
|
Sign up to set email alerts
|

Loss of tumour-specific ATM protein expression is an independent prognostic factor in early resected NSCLC

Abstract: Ataxia-telangiectasia mutated (ATM) is critical in maintaining genomic integrity. In response to DNA double-strand breaks, ATM phosphorylates downstream proteins involved in cell-cycle checkpoint arrest, DNA repair, and apoptosis. Here we investigate the frequency, and influence of ATM deficiency on outcome, in early-resected non-small cell lung cancer (NSCLC). Tissue microarrays, containing 165 formalin-fixed, paraffin-embedded resected NSCLC tumours from patients diagnosed at the Tom Baker Cancer Centre, Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Our findings also report frequent frameshift mutations in the ATM tumor suppressor gene leading to protein truncation in patients with lung adenocarcinoma. This is consistent with the fact that ATM mutations represent an early event in NSCLC pathogenesis and over 40% of lung adenocarcinomas are negative for ATM protein expression [ 22 ]. This gene has been found to be deficient serving as an independent prognostic factor associated with worse survival in stages II/III and chemotherapy resistance [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings also report frequent frameshift mutations in the ATM tumor suppressor gene leading to protein truncation in patients with lung adenocarcinoma. This is consistent with the fact that ATM mutations represent an early event in NSCLC pathogenesis and over 40% of lung adenocarcinomas are negative for ATM protein expression [ 22 ]. This gene has been found to be deficient serving as an independent prognostic factor associated with worse survival in stages II/III and chemotherapy resistance [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with the fact that ATM mutations represent an early event in NSCLC pathogenesis and over 40% of lung adenocarcinomas are negative for ATM protein expression [ 22 ]. This gene has been found to be deficient serving as an independent prognostic factor associated with worse survival in stages II/III and chemotherapy resistance [ 22 ]. Moreover, several ATM polymorphisms are risk factors for developing lung cancer in never smokers with low levels of carcinogen exposure [ 23 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…22,24,25 We also demonstrated that relative loss of ATM has clinical implications, conferring worse outcome and associated with improved benefit from cisplatin therapy. 26 Another potential target for PARP inhibitor therapy is lung cancer. Lung cancer is the leading cause of cancer death worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…AMPK shows an overall mutation rate of 2.1–3% (for the two isoforms of the catalytic subunit, respectively), ATM of 6%, DYRK2 of 2.7%, HIPK2 of 2.9%, p38α of 1.4%, and PKCδ of 1.7% (assessed via http://cbioportal.org). Reduced expression of the p53 Ser46 kinases in human tumors has been reported for four of the kinases: ATM in hormone‐negative breast cancer and non‐ small cell lung cancer; DYRK2 in colorectal cancer, hepatocellular carcinoma, and breast cancer; HIPK2 in oesophageal squamous cell carcinoma; and PKCδ in colon cancer . However, since the function of kinases depends on their specific activity and a number of Ser46 kinases, including DYRK2, HIPK2, PKCδ, and p38α, are regulated by their subcellular localization, it will be a complex task to determine their potential deregulation in cancer.…”
Section: Are P53 Ser46 Kinases Deregulated In Human Cancers?mentioning
confidence: 99%